A survey on Wireless Sensor Networks - Deepak Vats, Kulbushan, Avinash Sharma (International Journal of Advanced Science and Technology, 2020)
Owing to a large number of potential, useful and practical applications in various fields, wireless sensor networks (WSNs) have witness more investments and effort of researchers due to brisk development in the area of sensing, radio technology, communication and processing. Numerous areas of WSNs include radio technology, deployment, database querying, security, localization, data aggregation, middleware, architecture, synchronization, QoS and so on. In this text, a review of various issues related to design of wireless sensor networks and current area for research related to these issues are presented. The text provides a view on almost all topics of wireless sensor networks and our major motive, here is to give a good look at various areas for research in WSNs.